1955
DOI: 10.1042/bj0590268
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycete metabolism. Incorporation of 14C-labelled compounds into streptomycin

Abstract: Banks has supervised the maintenance of our radioactivity measuring apparatus, and we are grateful for his unfailing help in this respect. We are also pleased to acknowledge our indebtedness to Miss M. E. Lake, and Miss M. McKerrow who have assisted us in a few of these experiments, and to Mr M. P. Curwen for help and advice on statistical matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…The conversion by a S. griseus suspension of 'ICO2 to arginine labeled in the guanidino group was demonstrated a few years later (11 1). In 1955, Hunter and Hockenhull (59) reported that 14C glucose entered each of the three moieties of streptomycin to an equal extent but that the guanidino carbons were only poorly labeled. They further found that streptamine was not a true precursor since labeled streptamine entered all three moieties of the streptomycin molecule, the streptidine portion becoming no more radioactive than the other portions.…”
Section: )mentioning
confidence: 99%
“…The conversion by a S. griseus suspension of 'ICO2 to arginine labeled in the guanidino group was demonstrated a few years later (11 1). In 1955, Hunter and Hockenhull (59) reported that 14C glucose entered each of the three moieties of streptomycin to an equal extent but that the guanidino carbons were only poorly labeled. They further found that streptamine was not a true precursor since labeled streptamine entered all three moieties of the streptomycin molecule, the streptidine portion becoming no more radioactive than the other portions.…”
Section: )mentioning
confidence: 99%
“…The name highlights the fact that these antibiotics, in addition to an array of variously modified amino-sugars, contain an unusual cyclohexane derivative which can either be hexa-substituted as the streptamine unit (1) of streptomycin or penta-substituted as the 2-deoxystreptamine ring (2). The latter unit is present in neomycin (3) and more than fifty other related antibiotics.…”
mentioning
confidence: 99%
“…KAROW et al (1952) ftrst reported the preparation of 14C_la_ beled streptomycin by feeding labeled glucose or starch to the growing culture of S.griseus, then HUNTER and HOCKENHULL (1955) found that about 5% of D-[14C]glucose supplied to a 60-h culture of S. griseus was incorporated into streptomycin with the radioactivity equally distributed into the three subunits (streptidine, 34.1 %; streptose, 31.7%; and N-methyl-L-glucosamine, 34.8%). Thereafter, 14C-labeled compounds were used extensively as discussed in review articles by HOCKENHULL (1960), MENDICINO and PICKEN (1966), HORNER (1967), AKAMATSU (1968), andINAMINE (1970).…”
Section: Streptomycin and Bluensomycinmentioning
confidence: 99%
“…The mechanism remained obscure until recently. HUNTER and HOCKENHULL (1955) observed that 15.5% of N-methy1-L-[U-14C]glucosamine added to a 60-hr culture of S.griseus was incorporated into streptomycin, and about 75% of the incorporated radioactivity was found in the Nmethyl-L-glucosamine moiety. Incorporation of D-[U-14 C]glucose was very low (5%).…”
Section: B) Streptosementioning
confidence: 99%